Immune Dysregulation in IgG4-Related Disease - Liu, Jiachen; Yin, Wei; Westerberg, Lisa S.; Lee, Pamela; Gong, Quan; Chen, Yan; Dong, Lingli; Liu, Chaohong (Frontiers in Immunology, 2021)
Immunoglobin G4-related disease (IgG4-RD) is one of the newly discovered autoimmune diseases characterized by elevated serum IgG4 concentrations and multi-organ fibrosis. Despite considerable research and recent advances in the identification of underlying immunological processes, the etiology of this disease is still not clear. Adaptive immune cells, including different types of T and B cells, and cytokines secreted by these cells play a vital role in the pathogenesis of IgG4-RD. Antigen-presenting cells are stimulated by pathogens and, thus, contribute to the activation of naïve T cells and differentiation of different T cell subtypes, including helper T cells (Th1 and Th2), regulatory T cells, and T follicular helper cells. B cells are activated and transformed to plasma cells by T cell-secreted cytokines. Moreover, macrophages and some important factors (TGF-β) promote target organ fibrosis. Understanding the role of these cells and cytokines implicated in the pathogenesis of IgG4-RD will aid in developing strategies for future disease treatment and drug development. Here, we review the most recent insights on IgG4-RD, focusing on immune dysregulation involved in the pathogenesis of this autoimmune condition.